2019
DOI: 10.1038/s41586-019-1684-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod decline in grasslands and forests is associated with landscape-level drivers

Abstract: Recent reports on local extinctions of arthropod species1 and of massive declines in arthropod biomass 2 point to land-use intensification as a major driver of decreasing biodiversity. However, there are no multi-site time-series of arthropod occurrences across land-use intensity gradients to confirm causal relationships. Moreover, it remains unclear which land-use types and arthropod groups are affected and whether the observed declines in biomass and diversity are linked to one another and continue. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
776
9
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 945 publications
(836 citation statements)
references
References 37 publications
40
776
9
11
Order By: Relevance
“…A salient example of just how important cross-validation could be is the recent study of arthropod decline in Germany over a 10-year time series from 2008 to 2017 (Seibold et al, 2019). The overall time series trend, as well as region-specific and taxon-specific trends, are heavily influenced by one or two time-points in the data (see Fig.…”
Section: The Snapshot Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…A salient example of just how important cross-validation could be is the recent study of arthropod decline in Germany over a 10-year time series from 2008 to 2017 (Seibold et al, 2019). The overall time series trend, as well as region-specific and taxon-specific trends, are heavily influenced by one or two time-points in the data (see Fig.…”
Section: The Snapshot Effectmentioning
confidence: 99%
“…1 and fig. S3-1 in the study by Seibold et al, 2019). To their credit, the authors attempt a sensitivity analysis by dropping 1 year of the time series at a time, which "showed that the decline was influenced by, but not solely dependent on, high numbers of arthropods in 2008" (Seibold et al, 2019, p. 672).…”
Section: The Snapshot Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence points to widespread declines in insect populations over the past 30 years (Shortall et al, 2009;Hallman et al, 2017Hallman et al, , 2019Cardoso & Leather, 2019;Habel et al, 2019;Møller, 2019;Seibold et al, 2019). For example, in Germany, there has been a 75% decline in total flying insect biomass since 1989 (Hallman et al, 2017), while reductions of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Their long-lasting constructions, in grasslands in particular, often increase biodiversity, and impose patterns on the landscape which influence plants, vertebrates, invertebrates, and microbes over wide areas (e.g., Okullo & Moes, 2012;Schutz, Kretz, Dekoninick, Travani, & Risch, 2008). In intensively farmed landscapes, where the area of old grassland is declining and fragmented, biodiversity is under pressure, even on nature reserves (Hallmann et al, 2017;Seibold et al, 2019). Attempts are frequently made to introduce rare or iconic bird or mammalian species.…”
Section: Introductionmentioning
confidence: 99%